Apresentação pediátrica da síndrome antifosfolípide - Sato, Juliana de Oliveira [UNESP]; de Carvalho, Simone Manso [UNESP]; Magalhàes, Claudia Saad [UNESP] (My University, 2008)
Objective: To describe clinical and laboratorial features as well as outcome in a paediatric series with defined diagnosis of antiphospholipid syndrome. Methods: A descriptive-retrospective report from a pediatric tertiary referral, with case ascertainment by vascular events identification, either venous thrombosis or arterial occlusion, anti-cardiolipin antibodies (IgG and IgM) titres and lupus anticoagulant tests. Results: Five cases, being two boys and three girls, were identified in the last five years. Venous thrombosis occurred in brain sinus vessels (2), fibular (2), popliteal (1), femoral (1), intestinal (1) and renal (1) veins, followed by arterial occlusion in the gut (1), kidneys (1) halux (1) this resulted in digit gangrene as a recurrent event occurring during warfarin treatment. A spontaneous abortion occurred in an adolescent with thrombocytopenic purpura evolving into haemolytic anemia (Evans Syndrome) and bleeding fatal outcome. Laboratory investigation resulted in at least one positive titre of IgG and/or IgM anticardiolipin antibodies in all of the cases, being considered as primary antiphospholipid syndrome. Three cases have been followed under oral anticoagulation treatment. Conclusion: Cerebral and extremities venous thrombosis were the most frequent events in this series. This points to early diagnosis and team approach for investigation and treatment.
Paediatric antiphospholipid syndrome presentation
Keywords: Anticardiolipin antibodies; Antiphospholipid syndrome; Evans syndrome; Thrombosis